The Influence Of Comumunication and Leadership On Employee Performance At PT. Sinar Mitra Sepadan Finance Bengkulu City - Farizal Abdi Prakoso; Kharul Bahrun (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of communication and leadership on employee performance at PT. Sinar Mitra Sepadan Finance Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the employees of PT. Sinar Mitra Sepadan Finance Bengkulu City, which is precisely located on Jl. Salak Raya, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely total sampling. The number of respondents in this study were 40 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test.The results of this study can be concluded that the variable Communication has a positive effect on Employee Performance, Leadership has a positive effect on Employee Performance, and Communication and Leadership together have a significant effect on Employee Performance at PT. Sinar Mitra Sepadan Finance Bengkulu City.